Teknologi Pengembangan Jaringan Internet Untuk Sekolah di Pedesaan - Tengku Mohd Diansyah; Ilham Faisal; Dodi Siregar; Ade Zulkarnain Hasibuan; Sayuti Rahman (JPM: Jurnal Pengabdian Masyarakat, 2023)
In this community service activity we are developing an internet network that will be used by schools in rural areas, one of the areas in Stabat City in building this internet network we use the ubnt antenna which is reliable in spreading signals in the countryside and our goal is to build an internet network in the village, namely to help the community in obtaining information that is currently very fast and the obstacles that the surrounding community has are very difficult to connect to the internet network after the team pays attention to the problem because of the large number of palm trees that make it very difficult to get a signal in the village and even the school when the school is very fast. The obstacle that the village has is that the signal in the village is not up to 2 bars so that the surrounding community is very difficult to connect to the internet network after the team noticed the problem because of the large number of palm trees which made the signal very difficult to get by local residents and even schools currently have difficulty in the learning process, let alone accessing dapodik owned by the school which must be connected to the internet network.